LncRNA LINC01123-mediated impaired fracture healing through miR-134-5p/XIAP axis - Song Zhou; ZeWen Zheng; ChuanKai Zhang; Liang Hao; Qiang Chen; Ke Sun; Min Cai (Journal of Orthopaedic Surgery and Research)
Abstract Background The prolonged recovery and heightened discomfort associated with delayed fracture healing present substantial clinical challenges. Investigations into lncRNA-mediated pathways may provide novel biological targets for enhancing osseous regeneration and improving clinical outcomes. Aim The focus of this study is to elucidate the role and molecular mechanism of lncRNA LINC01123 (LINC01123) dysregulation in the osteogenic differentiation of osteoblasts. Methods Real-time quantitative polymerase chain reaction (RT-qPCR) determined LINC01123, miR-134-5p and XIAP levels in samples, alongside an assessment of osteogenic marker mRNA expression. The targeting relationships were verified by luciferase activity assay. The biological behavioural competence of the cells was assessed by cell counting kit-8 (CCK-8), flow cytometry, alizarin red staining assay, and western blot assay. Receiver operating characteristic (ROC) curve was applied to analyse the potential of LINC01123 in the diagnosis of delayed fracture healing. Results LINC01123 was overexpressed in patients experiencing delayed fractures and was sensitive in predicting the occurrence of delayed healing. As osteoblast differentiation progressed, the expression of LINC01123 and XIAP diminished, while the levels of miR-134-5p and ALP, OCN, RUNX2 mRNA were notably upregulated. Upregulation of LINC01123 reduced the levels of osteogenic biomarkers while suppressing cell viability and accelerating apoptosis, while miR-134-5p mimic partially reversed the inhibitory effect of LINC01123. Knockdown of XIAP partially mitigated the negative impact of silencing miR-134-5p on osteoblast differentiation and proliferation. Conclusion Elevated LINC01123 expression promotes delayed fracture healing through the miR-134-5p/XIAP pathway, positioning it as a candidate prognostic marker for progression of fracture healing response. Clinical trial number Not applicable.